THE RESULTS OF INTERVAL TRAINING AND CONTINUOUS TRAINING PROGRAMS TOWARDS MAXIMAL OXYGEN CONSUMPTION RATES OF FOOTBALL PLAYERS - Sompan, Apiwat; Dokmaikhao , Athiwat (Academic Journal of Thailand National Sports University, 2022)
This research aims to investigate and compare between the results of interval training and continuous training programs, as well as the differences of training times between interval training and continuous training programs towards maximal oxygen consumption rates of football players. The samples were forty - five male football players aged between 14 - 16 years old selected by purposive random sampling. They were divided into three groups by random assignment: Group 1 with the conventional training program only; Group 2 with the conventional program with the interval training program; and Group 3 with the conventional program with the continuous training program. All of them were trained three days a week for eight weeks and were tested to figure out the maximal oxygen consumption rates during the pre - training, after the fourth and the eighth weeks of training. Data analysis with mean, standard deviation, One - Way Analysis of Variance with repeated measure, and the Least Significant Difference method (LSD). The findings revealed as follows: Mean and Standard Deviation of maximal oxygen consumption rates before training of all three groups at before training, after training at Week 4 and after training at Week 8 showed that Group 1 (2.56 ± 0.11, 2.56± 0.11, 2.57 ± 0.08) consumed less than Group 2 (2.56 ± 0.11, 3.00± 0.09, 3.46 ± 0.11) and Group 3 (2.56 ± 0.07, 2.59 ± 0.07, 2.79 ± 0.10) respectively, and Group 3 most consumed. Between groups, after the fourth - week significant differences in maximal oxygen consumption rate were found between Group 1 and Group 2, and between Group 2 and Group 3; moreover, after the eighth week, significant differences were found between Group 1 and Group 2 & Group 3, and between Group 2 and Group 3 at the level of .05. Within groups, in Group 1 no significant differences in maximal oxygen consumption rates were found between pre - training, after the fourth and the eighth weeks while in Group 2 significant differences were found between pre – training and the fourth and the eighth weeks, and between the fourth week and the eighth week at the level of .05, and in Group 3 significant differences were found between pre - training and the fourth and the eighth weeks, and between the fourth week and the eighth week at the level of .05. Training with the interval training and continuous training programs had an effect on maximal oxygen consumption rates; also, duration of longer duration of training can develop maximal oxygen consumption.